2014
DOI: 10.1097/qai.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

Disrespect and Abuse During Childbirth in Tanzania

Abstract: Introduction:HIV-related stigma and discrimination and disrespect and abuse during childbirth are barriers to use of essential maternal and HIV health services. Greater understanding of the relationship between HIV status and disrespect and abuse during childbirth is required to design interventions to promote women's rights and to increase uptake of and retention in health services; however, few comparative studies of women living with HIV (WLWH) and HIV-negative women exist.Methods:Mixed methods included int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(106 citation statements)
references
References 9 publications
7
92
7
Order By: Relevance
“…This was a little higher than an observational study in a hospital in Tanzania, where providers used non-dignified language with 5.6% and shouted at 6.6% of HIV-negative women while taking their medical history [45]. An exit interview study conducted in Ethiopia and Kenya showed 14% women in Addis Ababa hospitals [43] and 18% of women in Kenya were verbally abused [42].…”
Section: Discussionmentioning
confidence: 99%
“…This was a little higher than an observational study in a hospital in Tanzania, where providers used non-dignified language with 5.6% and shouted at 6.6% of HIV-negative women while taking their medical history [45]. An exit interview study conducted in Ethiopia and Kenya showed 14% women in Addis Ababa hospitals [43] and 18% of women in Kenya were verbally abused [42].…”
Section: Discussionmentioning
confidence: 99%
“…In the Dar es Salaam region, over 90 % of the population delivers in a healthcare facility [19]. The study facility is located in the poorest district in Dar es Salaam and serves as a regional referral hospital for complicated pregnancy and maternity cases to over 70 health facilities in the district.…”
Section: Methodsmentioning
confidence: 99%
“…This is part of the larger study that aimed to test interventions to reduce occurrence of D&A during childbirth, of which some of the findings have already been published [19]. …”
Section: Introductionmentioning
confidence: 99%
“…At least four recent studies have examined PMTCT adherence and engagement in Tanzania (10, 20, 27, 28). A cohort study with 120 mother-child pairs, conducted in 2011 before Option A implementation, found only 10 pairs (8.3%) achieved at least 80% adherence rates in all PMTCT phases (before, during, and after delivery); one mother-child pair (0.8%) achieved a 95% adherence level for the entire PMTCT intervention (27).…”
Section: Introductionmentioning
confidence: 99%
“…A 2014 qualitative study in northern Tanzania highlighted the importance of patient-provider relationships in PMTCT engagement and noted that imbalances of power, unclear communication, disrespectful statements, discriminatory treatment, and inadequate counseling by providers undermined PMTCT clients’ trust in the health care system (10). However, a more recent mixed-methods study based in an urban referral facility in Dar es Salaam found no statistically significant difference in the experience of disrespect or abuse by HIV serostatus; the authors underscored that the overall prevalence of disrespect and abuse is high, indicating “a serious problem” in the maternal health sector generally (28). …”
Section: Introductionmentioning
confidence: 99%